2001
DOI: 10.4049/jimmunol.167.3.1693
|View full text |Cite
|
Sign up to set email alerts
|

Increased Entry into the IFN-γ Effector Pathway by CD4+ T Cells Selected by I-Ag7 on a Nonobese Diabetic Versus C57BL/6 Genetic Background

Abstract: IFN-γ-mediated Th1 effects play a major role in the pathogenesis of autoimmune diabetes in nonobese diabetic (NOD) mice. We analyzed functional responses of CD4+ T cells from NOD and B6.G7 MHC congenic mice, which share the H2g7 MHC region but differ in their non-MHC genetic background. T cells from each strain proliferated equally to panstimulation with T cell lectins as well as to stimulation with glutamic acid decarboxylase 524–543 (self) and hen egg lysozyme 11–23 (foreign) I-Ag7-binding peptide epitopes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 72 publications
(73 reference statements)
6
18
0
Order By: Relevance
“…As we previously published, we have found no evidence that the NOD T cell abnormality was due to increased preactivated or memory autoreactive T cells in the NOD periphery in these 8-wkold mice (35). The results predict that the same phenotype should be found in a nondiabetes prone strain with the NOD non-MHC background.…”
Section: Nodh2 B Cd4 ϩ T Cells Demonstrate the Nod Intrinsic Th1 Phesupporting
confidence: 59%
See 1 more Smart Citation
“…As we previously published, we have found no evidence that the NOD T cell abnormality was due to increased preactivated or memory autoreactive T cells in the NOD periphery in these 8-wkold mice (35). The results predict that the same phenotype should be found in a nondiabetes prone strain with the NOD non-MHC background.…”
Section: Nodh2 B Cd4 ϩ T Cells Demonstrate the Nod Intrinsic Th1 Phesupporting
confidence: 59%
“…Furthermore, this phenotype was mapped near to the Idd5 and Idd13 loci (34). We have recently shown that T cells selected by I-A g7 on an NOD, but not B6, genetic background demonstrated increased entry into the IFN-␥ effector pathway (35). The role of the NOD non-MHC genetic background was confirmed by showing that T cells from NOD.H2…”
Section: Increased Nonobese Diabetic Th1:th2 (Ifn-␥:il-4) Ratio Is Cd4mentioning
confidence: 50%
“…Evidence suggests that ␤ cell destruction is mediated, at least in part, by effector CD4 ϩ T cells that preferentially secrete IFN-␥ and TNF-␣ (18,19). NOD CD4 ϩ T cells have been shown to have an increased propensity to become effector Th1 cells in tissue culture assays (20). We wanted to determine whether Th1 differentiation by NOD T cells had the same cytokine requirements as found in other strains.…”
Section: N Aïve Cd4mentioning
confidence: 99%
“…Studies in tissue culture models, by us and others, demonstrate that, in contrast to other murine strains, CD4 ϩ T cells from the autoimmune prone nonobese diabetic (NOD) strain are genetically programmed to use IL-2 as a driving cytokine to differentiate into IFN-␥-producing effector T cells (21)(22)(23). Thus, an antigen stimulus is sufficient to drive both T cell proliferation and Th1 differentiation.…”
mentioning
confidence: 99%